A Comparative Analysis of India's Two Leading Digital Learning Platforms: NPTEL and SWAYAM - Amit Kishore; Amita Singh; Rajeev Roushan (International Journal of Atmosphere, 2024)
In recent years, India has witnessed a transformative shift in its educational landscape with the advent of digital learning platformsthe role of MOOCs is extremely important in this direction.. This revolution has been propelled by the increasing accessibility of the internet and a growing demand for flexible, inclusive, and technology-driven education. MOOC learning platforms have the potential to transform the educational landscape in India, making quality education more accessible, flexible, and responsive to the evolving needs of learners, educators, and the broader society. Today, MOOCs have become an integral part of the Indian education system, providing accessible and flexible learning opportunities for learners of all ages and backgrounds. The continued evolution and expansion of platforms like NPTEL and SWAYAM, along with the participation of Indian learners in global MOOC platforms, have contributed to the increasing prominence of MOOCs in India. This study presents the current status of MOOC programs in India and a comparison of NPTEL and SWAYAM.
Keywords: Massive Open Online Courses; NPTEL; Online learning; SWAYAM; digital learning